Clasroom intervention in inhibitory control in children with and without language disorders - Aguilar-Mediavilla, Eva; Guirado-Moreno, Jorge Luis; Sánchez-Azanza, Víctor; Adrover-Roig, Daniel; Valera-Pozo, Mario (Revista de Investigación en Logopedia, 2021)
The aim of this work was to assess the effect of classroom intervention in the inhibitory control carried out in different classrooms of primary scholars (9-11 years) that had students with Development Language Disorder (n = 5) or dyslexia (n = 4) and their classmates without difficulties (n = 6). The design followed a pre-post intervention model over verbal fluency, phonological memory and inhibitory control. The intervention consisted of eight 10-minute sessions for the entire class group, two per week during four weeks, plus a 1-hour long session with small groups in the middle of the sessions, with activities based on different inhibitory control tasks (“Stroop”, “Go-no go”, “Plots”, “Simon”,…). Children with DLD and dyslexia showed a lower phonological memory score before the intervention. The intervention only had a slight effect on phonological memory in all the groups. However, the post-intervention comparison between groups showed lower scores of verbal fluency and inhibitory control in the DLD group compared to the other two, which may indicate a possible improvement in these variables in dyslexia and typical development children groups. In conclusion, the intervention had a scarce effect, especially in the DLD group. Further, works including a larger number of participants and intervention sessions might help elucidate reasons why the present work does not show specific improvements in inhibitory control and fluency after the intervention.